Risk Factors for Invasive Fungal Disease in Pediatric Cancer and Hematopoietic Stem Cell Transplantation: A Systematic Review. (26th May 2017) - Fisher, Brian T; Robinson, Paula D; Lehrnbecher, Thomas; Steinbach, William J; Zaoutis, Theoklis E; Phillips, Bob; Sung, Lillian
Abstract: Background: Although a number of risk factors have been associated with invasive fungal disease (IFD), a systematic review of the literature to document pediatric-specific factors has not been performed. Methods: We used the Ovid SP platform to search Medline, Medline In-Process, and Embase for studies that identified risk factors for IFD in children with cancer or those who undergo hematopoietic stem cell transplantation (HSCT). We included studies if they consisted of children or adolescents (<25 years) who were receiving treatment for cancer or undergoing HSCT and if the study evaluated risk factors among patients with and those without IFD. Results: Among the 3566 studies screened, 22 studies were included. A number of pediatric factors commonly associated with an increased risk for IFD were confirmed, including prolonged neutropenia, high-dose steroid exposure, intensive-timing chemotherapy for acute myeloid leukemia, and acute and chronic graft-versus-host disease. Increasing age, a factor not commonly associated with IFD risk, was identified as a risk factor in multiple published cohorts. Conclusions: With this systematic review, we have confirmed IFD risk factors that are considered routinely in daily clinical practice. Increasing age should also be considered when assessing patient risk for IFD. Future efforts should focus on defining more precise thresholds for a particular risk factor (ie, age, neutropenia duration) and on development of prediction rules inclusive of individual factors to further refine the risk prediction.